Military Diplomacy: Role of Nepali Army in Reshaping Nepalese foreign Policy - Kafle, Sujan (Unity Journal, 2022)
Development of the concept of foreign policy began with the unification of Nepal which can be reflected through the Prithvi Narayan Shah's teaching (Divya Upadesh). Foreign policy is an external display of the nation's internal strengths and aspirations. Foreign policy is extension of domestic policy, how the relation is maintained with international community? How our international relation is guided? Country’s foreign policy is determined on the basis of various principles through diplomatic channels. While in the developing world context, military diplomacy is also one of the tools to determine the foreign policy of Nepal. Military diplomacy is a peaceful use of military in field of diplomacy to achieve the goals of national foreign policy. This research article examines the role of the Nepali Army in shaping up the Nepalese foreign policy tracing its importance’s from the historical perceptive. What can be the role of the Nepali Army in strengthening the country’s foreign policy? This paper further elucidates history about the military diplomacy of Nepal and also focuses on the role played by the Nepali Army in the UN peace keeping mission making this as one of the parameters for determents of foreign policy of Nepal. Also, Military attachés in many of the foreign countries with their vital roles have been able to reshape Nepal’s relations with international communities through their strengthened military diplomacy those agents and organizations. This study is methodologically based on the collected information from secondary sources, journal, article, and study of activities of the Nepali Army.